Layout and Design Techniques of Cross Section for the Large Immersed Tunnel. (2016) - Zhigang, Zhang; Wei, Lin; Hai, Ji; Xiaodong, Liu
Abstract: Layout and structure design of cross-section are the key matters that shall be determined in the design of immersed tunnel as soon as possible, and are the general works at the stage of feasibility design. In recent years, immersed tunnel confronts more complex engineering conditions and higher technical standards; there exists longer and larger immersed tunnels used as vehicle passages such as Oresund Link between Demark and Sweden, Busan Link in South Korea, and HongKong-Zhuhai-Macau(HZM) Link, which is under construction in China. The cross-section design has a significant effect upon project scale, technical difficulty, construction cost and so on, hence it becomes the most essential and difficult part in the design of immersed tunnel. Based on the practical experience of the immersed tunnel design and construction of the Hongkong-Zhuhai-Macao Link, the main influential factors of the HZM long and large immersed tunnel, including clearance, ventilation, fire fighting and rescue, decoration, bearingforce, stabilization of floating status and construction tolerance, are summarized.And all optional layouts and their suitability of the immersed tunnel cross section are analyzed. Then the tunnel cross section of two traffic bores and one central gallery was proposed for HZM immersed tunnel by the designer based on the combination of longitudinal ventilation and emphatic smoke extraction scheme. And the detailed parameters of tunnel cross section proposed for HZM immersed tunnel were provided. Finally, some personal understandings and thoughts on the large immersed tunnel were provided as an discussion and for the reference of the designers of cross section of the immersed tunnel of similar type.